Realisation of the Knowledge Management Process in Study - related Performance of Academic Departments - Misiūnaitė - Bačiauskienė, Eglė; Jucevičienė, Palmira (Pedagogika, 2014)
The context of knowledge management determines the following research question: how theoretical constructs of knowledge management are realised in the performance of academic departments? The research aim is to identify the implementation of study-related knowledge management process at academic department. The empirical research is based on the case study strategy. After targeted selection of cases, in-depth interviews were carried out at two academic departments, where groups of experts had been identified. The collected data were processed by criterion-based analysis. The Department X possesses expertise in education and methodological competence in curriculum construction and study process realisation; study-related processes of collective and individual knowledge management are articulated by study-related terminology and informal identification of knowledge in the process of social interaction dominates here; unfortunately little coordination is given to the acquisition, dissemination, creation, storage and application of knowledge. The Department Y informally reduces the study-related knowledge to the concept of professionalism and knowledge of the study programme content; methodological competence of designing and implementing a study programme (module) is referred to as developing. In this context, the need for knowledge acquisition is realised by attracting external expert knowledge. At this Department, the process of study related knowledge is not systemic and strongly coordinated; individual not collective efforts prevail. Summarising the analysis of the two case-studies, it is evident that a formalized system of knowledge management has not been yet created and implemented in the departments. However, the educational and subject-related competences of the department lead to unintentional knowledge management process that is naturally taking place through the process of studies management with the prevailing non-formal activities of organizational knowledge identification, acquisition, creation, dissemination, storage and application.